Use of two‐dimensional speckle tracking echocardiography to predict cardiac events: Comparison of patients with acute myocardial infarction and chronic coronary artery disease. Issue 1 (23rd January 2018) - Scharrenbroich, Jörg; Hamada, Sandra; Keszei, Andras; Schröder, Jörg; Napp, Andreas; Almalla, Mohammad; Becker, Michael; Altiok, Ertunc
Abstract : Background: Two‐dimensional speckle strain (2D STE) echocardiography can aid in the prognosis of acute myocardial infarction (AMI) and chronic coronary artery disease (CAD). Hypothesis: Differences occur in the prediction of cardiac events using 2D STE in AMI vs CAD patients. Methods: In this prospective study, 94 patients with a first AMI and successful revascularization, and 137 patients with stable CAD after complete revascularization were included. In all patients, we performed echocardiography and myocardial deformation analysis for layer‐specific global circumferential strain (GCS) and longitudinal strain. Receiver operating characteristic (ROC) curve analysis was used to predict the presence of a cardiac event using strain values and baseline characteristics in different regression models. Results: Patients were followed for 3.6 ± 0.8 years. Strain parameters in AMI and CAD patients were significantly different with respect to the occurrence of a cardiac event. Frequency of diabetes and hypertension was associated with the presence of a cardiac event in CAD patients. Furthermore, in CAD patients, ROC analysis demonstrated that the addition of endocardial GCS to baseline characteristics and ejection fraction to a regression model significantly improved the prediction of cardiac events (area under curve = 0.86, cutoff value: 20%, sensitivity: 79%, specificity: 84%). In contrast, the addition of strain parameters in AMI patients did not increase the prediction power for cardiac events. Conclusions: Global strain parameters by 2D STE may be useful for the prediction of cardiac events in patients with CAD but add no supplemental information to baseline characteristic and ejection fraction in patients with AMI.